Tyrian purple: the first four thousand years. (1st June 2013) - Cooksey, Chris
Some of the long history of shellfish purple is recounted. Understanding how the dye is produced from molluscs, the composition of the pigment and the chemistry involved has only been achieved as a result of the advances in analytical chemistry in the twentieth century, but some mysteries remain. Other diverse aspects such as the taste of the molluscs, the actual colour of the dye, the smell associated with the production and even the application in photography contribute to the fascination of the subject.